STRONG CONVERGENCE OF A NEW TWO-STEP ITERATIVE SCHEME FOR TWO QUASI-NONEXPANSIVE MULTI-VALUED MAPS IN BANACH SPACES - Cholamjiak, W.; Suantai, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In this paper, a new two-step iterative scheme is introduced for two quasi-nonexpansivemulti-valued maps in Banach spaces. Strong convergence theorem of the purposed iterativescheme is established for quasi-nonexpansive multi-valued maps in Banach spaces. The resultobtained in this paper improve and extend the corresponding one announced by Shahzad andZegeye [N. Shahzad, H. Zegeye, On Mann and Ishikawa iteration schemes for multi-valuedmaps in Banach spaces, Nonlinear Analysis 71 (2009) 838-844.].